Application of components inexorables on the stage of sanitation in the context of the execution of informal mining - Chávez de la Cruz, Norly Elith (2016)
The present article seeks to summarize and set out the legislative development of the Formalization Process of the Small-Scale Mining and Artisanal Mining, it has been established with the aim to combat illegal mining. In that sense, this research analyzed from all fonts the real situation of individuals in the process of formalizing compared with current regulations, to review the issues related to authorization certificates or permits, and other newly regulated requirements, which will have attributed the name “Inexorable Components” under the formalization process regulated by Legislative Decree N.o 1105, being of compliance required to obtain the Authorization of Start or Re-start Operations that allows the change of status of the mining rights holder from “Formalizing Process” to “Formalized Subject”. Finally, the article will reveal the implications and problems that have been noticed in the course of the execution of the process, highlighting their strengths and weaknesses; with